Analisis relasi dan fungsi: perspektif matematika diskrit dalam hubungan sosial - Aldin, Ammar Dzaky Rosich (Maliki Interdisciplinary Journal, 2025)
Discrete mathematics is a branch of mathematics that focuses on distinct objects, one of which is the concept of relations and functions. A relation is used to describe connections between individuals or groups, while a function is a special type of relation that maps each element of the domain to exactly one element of the codomain. This study aims to explain the relevance of relations and functions to social life phenomena, thus providing a more concrete and applicable understanding. The method used is literature review and descriptive analysis by examining social examples such as family relations, friendships, education systems, organizations, economics, and social media. The results show that relations play a role in modeling general patterns of social interaction, whereas functions represent the mapping of identities or social roles in a unique and structured way. Therefore, it can be concluded that relations and functions are not only theoretical concepts in discrete mathematics but also have practical contributions in understanding and organizing modern social life.